THE DEVIATION-FROM-EQUILIBRIUM EFFECT ON DISSOLUTION RATE AND ON APPARENT VARIATIONS IN ACTIVATION ENERGY - V. GIBBSITE SOLUBILITY AT 50°C AND PH 3 TO 9 IN 0.1 MOLAL NACL SOLUTIONS, A GENERAL MODEL FOR ALUMINUM SPECIATION, AND ANALYTICAL METHODS - Cama J.; Ayora C.; Lasaga A.C. (My University, 1999)
Dissolution rates of minerals depend on several factors. Among them, the factor measuring the deviation of the solution from equilibrium has not been sufficiently investigated. The dissolution rate of kaolinite as it would be ''measured'' by experiments has been calculated from an expression deduced from experiments. The calculations show that the ''measured'' dissolution rate may deviate significantly from that corresponding to a far-from-equilibrium solution. The deviation increases as temperature increases, the ratio between flow rate and reactive surface decreases, and pH tends to neutral. This deviation leads to dramatic changes in activation energy as deduced from a regression of a limited number of experiments. Activation energy values tend to decrease apparently as pH tends to neutral, exactly as suggested in the literature for some silicates. Therefore, the deviation-from-equilibrium factor may significantly affect measured dissolution rates, and must be taken into account in obtaining the activation energy values of dissolution/precipitation reactions.